On solving the split generalized equilibrium problem and the fixed point problem for a countable family of nonexpansive multivalued mappings - Phuengrattana, Withun; Lerkchaiyaphum, Kritsada (Fixed point theory and applications (Hindawi Publishing Corporation), 2018)
We consider the split generalized equilibrium problem and the fixed point problem for a countable family of nonexpansive multivalued mappings in real Hilbert spaces. Then, using the shrinking projection method, we prove a strong convergence theorem for finding a common solution of the considered problems. A numerical example is presented to illustrate the convergence result. Our results improve and extend the corresponding results in the literature.